Concise Encyclopaedia of Bioinformatics and Computational Biology
Concise Encyclopaedia of Bioinformatics and Computational Biology, 2nd Edition is a fully revised and updated version of this acclaimed resource.Concise Encyclopaedia of Bioinformatics and Computational Biology, 2nd Edition provides definitions and often explanations of over 600 words, phrases and concepts relating to this fast-moving and exciting field, offering a convenient, one-stop summary of the core knowledge in the area. This second edition is an invaluable resource for students, researchers and academics.